Issues in Methodology of Islamic Thought: Safar 9-12, 1410/September 11-14, 1989 (American Journal of Islam and Society, 1989)
During the period from Safar 9-12, 1410 H. / September 11-14,1989 A.D.,a seminar on the "Issues in Methodology of Islamic Thought" was held atAmir AM al Qadir University of Islamic Studies (Qusantinah, Algeria). Theseminar was organized by the university in conjunction with the InternationalInstitute of Islamic Thought (Washington, D.C.). A group of professors andstudents of both sexes from Amir Abd al Qadir University, as well as fromthe Central University, participated in the seminar activities. The openingsession was attended by representatives from Qusantinah Province, the NationalLiberation Front, the Municipal Council, and the Religious Committee.Speeches were delivered by Dr. 'Ammar al Talibi, the University Presidentand Chairman of the seminar; Dr. Gamal El-Din Attia, Academic Advisorof the International Institute of Islamic Thought and convenor of theseminar; and by Dr. Muhammad 'AM al Hadi Abu Ridah representing theguests of the seminar.The seminar included seven panels where twenty-one research papers,prepared for the seminar, were presented and discussed. These research paperscovered the following topics:1- Inference Methodology in the Qur'an: A Response to the Opponentsof Faith, by Dr. Ahmad 'Atwah.2- The Elements of Scientific Methodology in the Qur'an andal Sunnah, by Dr. Ghawi 'Inayah.3 - Muslim Methodology in Islamic Theology, by Dr. FawqiyahHusayn.4 - The Methodology of Ideology in the Light of ContemporaryScientific Advances, by Dr. Muhammad Abd al Sattar Nassar.5- An Overview of the Methodology of Recording History, byDr. 'Abd al Halim 'Uways.6- The Methodology of the Principles of Jurisprudence, by Dr.Abd al Hamid Madkur.7- The Crises of Methodology in Modem Ideological Studies,by Dr. Muhammad Kamal al Din Imam.8- The Scientific Methodology and Spirit of Ibn Khaldun andIts Relation to Islam, by Dr. 'Imad al Din Khalil ...